Intrasaccular neck-bridging: A technical note on Nautilus-assisted coiling of wide-necked cerebral aneurysms. Feasibility study, immediate and early angiographic results. Issue 6 (December 2022) - Sirakov, A; Bhogal, P; Sirakova, K; Minkin, K; Ninov, K; Karakostov, V; Sirakov, S
Purpose: Various adjunctive devices have been reported to be helpful during the endovascular coiling of complex, wide-necked cerebral aneurysms. This study aimed to describe the utilization of a recently introduced intrasaccular neck-bridging implant specifically designed to facilitate coil embolization. Methods: We retrospectively reviewed eight consecutive patients who underwent treatment for intracranial aneurysms with the Nautilus intrasaccular bridging system between February 2022 to May 2022. We evaluated the angiographic appearances of treated aneurysms at the end of the procedure and early follow-up, the clinical status and complications. Results: Eight patients with eight cerebral aneurysms (3 men and 5 women, mean age 52.8 years (range 39–66) were analyzed. Five of the treated aneurysms were managed in an acute case scenario. There were no technical difficulties while executing the technique. No other procedural adverse events were documented. Immediate complete occlusion of the aneurysm was seen in 6 patients, neck remnant in 1 and stable aneurysm reperfusion in one case. Early radiological follow-up was available in five patients, and the observed occlusion rates were – RR class I in all radiologically screened aneurysms. Conclusion: Nautilus-assisted coil embolization represents a rapid and safe solution for complex cerebral aneurysms. In our opinion this device symbolizes a significant step forward in treating intracranial aneurysms. We believe that the technique's actual value consists of the fact that the device is fully compatible with the modern low-profile microcatheter technology and does not involve the need for antiplatelet medications.